Amalgam Alternatives: Cost-Effectiveness and Value of Information Analysis. (November 2018) - Schwendicke, F.; Göstemeyer, G.; Stolpe, M.; Krois, J.
We aimed to assess the cost-effectiveness of amalgam alternatives—namely, incrementally placed composites (IComp), composites placed in bulk (BComp), and glass ionomer cements (GIC). In a sensitivity analysis, we also included composite inlays (CompI) and incrementally placed bulk-fills (IBComp). Moreover, the value of information (VOI) regarding the effectiveness of all strategies was determined. A mixed public-private-payer perspective in the context of Germany was adopted. Bayesian network meta-analyses were performed to yield effectiveness estimates (relative risk [RR] of failure). A 3-surfaced restoration on a permanent molar in initially 30-y-old patients was followed over patients' lifetime using a Markov model. Restorative and endodontic complications were modeled; our outcome parameter was the years of tooth retention. Costs were derived from insurance fee items. Monte Carlo microsimulations were used to estimate cost-effectiveness, cost-effectiveness acceptability, and VOI. Initially, BComp/GIC were less costly (110.11 euros) than IComp (146.82 euros) but also more prone to failures (RRs [95% credible intervals (CrI)] were 1.6 [0.8 to 3.4] for BComp and 1.3 [0.5 to 5.6] for GIC). When following patients over their lifetime, IComp was most effective (mean [SD], 41.9 [1] years) and least costly (2, 076 [135] euros), hence dominating both BComp (40.5 [1] years; 2, 284 [126] euros) and GIC (41.2 years; 2, 177 [126] euros) in 90% of simulations. Eliminating the uncertainty around the effectiveness of the strategies was worth 3.99 euros per restoration, translating into annual economic savings of 87.8 million euros for payers. Including CompI and IBComp into our analyses had only a minimal impact, and our findings were robust in further sensitivity analyses. In conclusion, the initial savings by BComp/GIC compared with IComp are very likely to be compensated by the higher risk of failures and costs for retreatments. CompI and IBComp do not seem cost-effective. All alternatives are likely to be inferior to amalgam. The VOI was considerable, and future studies may yield significant economic benefits.